Patients with Normal Coronary Arteries Via Angiography: The Relationship Between Slow Coronary Flow and Serglycin - Bolayir, Hasan Ata (Cardiology and Cardiovascular Medicine, 2018)
Background: Slow coronary flow (SCF) is an angiographic finding characterized with delayed opacification of epicardial coronary arteries without obstructive coronary disease. Several mechanisms have been proposed for SCF phenomenon, including inflammation. Serglycin has an important role in the inflammatory status. In this study, we aimed to investigate the relationship between serglycin and SCF phenomenon in patients with angiographically normal coronary arteries. Method: A total of 174 individuals [n=92 with SCF and n=82 with NCF (normal coronary flow)] who underwent coronary angiography with suspicion of coronary artery disease, and had angiographically normal coronary arteries of varying coronary flow rates without any atherosclerotic lesion were enrolled. SCF was defined according to TIMI frame count (TFC) method. Results: Baseline demographic properties were similar in both groups. Those with SCF had significantly increased average serum high sensitivity C-reactive protein (hsCRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), vascular cell adhesion protein-1 (VCAM-1) and serglycin values than those of NCF (hsCRP: 2.4 ± 0.4 vs. 1.1 ± 0.2mg/dL, p=0.006, TNF-α :5.95 ± 0.9 vs. 3.17 ± 0.6 pg/mL, p<0.001, IL-6: 22.97 ± 1.9 vs. 14.23 ± 1.1 pg/mL, p=0.002,VCAM-1:21.32 ± 3.9 vs. 10.1 ± 2.2 pg/mL, p<0.001, serglycin: 21.1 ± 2.9 vs. 12.3 ± 3.1 ng/mL, p<0.001, respectively).The ROC curve analysis showed a moderate diagnostic value of plasma serglycin levels for identifying patients with SCF from those with NCF (AUC = 0.804, 95% CI: 0.735–0.872, P < 0.001), it was better than that of plasma hsCRP levels (AUC = 0.617, 95% CI: 0.533–0.702, P = 0.010) and similar with that of plasma TNF-α levels (AUC = 0.785, 95% CI: 0.718–0.853, P < 0.001). C